KESANTUNAN BERBAHASA DALAM PESAN WHATSAPP MAHASISWA YANG DITUJUKAN KEPADA DOSEN - Enggar Dhian Pratamanti; Rati Riana; Sofyandanu Setiadi (Jurnal Dinamika Sosial Budaya, 2017)
A relationship between student and lecturer need communication, whether it is inside or outside a campus. This communication should be in politeness boundaries, although it is uttered in a semiformal situation. The emerge of social media as a result of a technology development affects the communication between student and lecturer. This research examines the speech act and politeness used by student to communicate with his lecturer through Whatsapp. This study aims to describe and analyze the politeness used by student when he communicates with his lecturer using Whatsapp and to describe and analyze the politeness deviation used by student to communicate with his lecturer using Whatsapp. The data source comes from Whatsapp chatting application. The data is the student’s utterance which is used to communicate with the lecturer through Whatsapp. That data is used to collect the information so that it can be analyzed. Technique of collecting data uses observation method, note-taking technique, and interview. Qualitative method is used to analyze the data. Based on the analyses, it is found that there are many of the student’s utterance used to communicate with the lecturer using Whatsapp is not fulfill the politeness value. In that utterance, many politeness deviation were found such as the use of slank, the out of context discussion, the way to deliver intention impolitely, and the inappropriate of using paralinguistic aspect.